STRATEGI KEPALA SEKOLAH MEGIMPLEMENTASIKAN KURIKULUM CAMBRIDGE UNTUK MEMBENTUK SISWA BERDAYA SAING INTERNASIONAL DI SEKOLAH MENENGAH PERTAMA THURSINA INTERNASIONAL ISLAMIC BOARDING SCHOOL MALANG - Hayyi, Mila; Zaen , Basri; Hambali, Muh. (re-JIEM (Research Journal of Islamic Education Management), 2022)
This research aims to describe the strategy of having a master’s in implementing the Cambridge curriculum to shep studentâ€™s potential to compete globally at SMP Thursina Internasional Islamic Boarding School Malang. The focuses of the study involve (1) the characteristics of studentsâ€™ potential for international competitions. (2) the strategy from hand master in implementing Cambridge curriculum to establish students in competing Globally. (3) the model of strategy from the headmaster in implementing the Cambridge curriculum to establish students to compete Globally. The findings show that 1) the characteristics of students with good potential to compete Globally can be observed from the foreign language proficiency, academic achievement for both national and international levels, and kind of Extracurricular program provided. (2) strategy in implementing Cambridge curriculum through the application of management function which includes: planning, organization, implementation, and Evaluation. 3) model of strategy from headmaster in implementing Cambridge curriculum implementation and overseas program, Quality Control, and human resource research.